(untitled) (Biocenosis, 2026)
Present a teaching guide aimed at secondary school teachers, focused on addressing water as a common good from the perspective of Education for Sustainable Development. The aim is to strengthen teachers’ skills and knowledge in innovation and instructional strategies, so they can respond to their students’ realities and local contexts, such as the limited and conditional access to potable water in the community of Los Ángeles de Pital (San Carlos, Alajuela, Costa Rica. The proposal integrates participatory methodologies, situated learning and community engagement, organized into five sessions that address conceptual, ecological and social dimensions of water resources. Critical reflection on the use, access, and management of water is promoted through strategies such as body mapping, water footprint analysis, and dialogue with local stakeholders. The guide is presented in an accessible format that allows for adaptation to different educational contexts, promoting pedagogical mediation, and the development of environmental awareness.